Observation of off-axis sawtooth oscillations during the presence of nonlinear mode couplings in HL-2A NBI heated plasmas. (11th August 2021) - Shi, P.W.; Chen, W.; Wang, Z.X.; Qiu, Z.Y.; Shi, Z.B.; Yu, L.M.; Yang, Z.C.; Zhong, W.L.; Jiang, M.; Wang, T.B.; He, X.X.; Liang, S.Y.; et al.
Abstract: Off-axis sawtooth oscillations during the presence of nonlinear coupling between toroidal Alfvén eigenmodes (TAEs) and tearing mode are firstly observed in the plasma without two q = 2 rational surfaces on HL-2A tokamak. Those low frequency oscillations always take place followed by nonlinear interaction processes and the off-axis features have been confirmed by multiple diagnostics, such as soft x-ray arrays and electron cyclotron emission imaging systems. A possible physical mechanism is proposed for interpretation of those off-axis oscillations. That is, nonlinear interaction between TAEs and tearing mode causes significant losses of fast ions though the spacial overlapped global mode structure, then makes a drop in torque and leads to rotation braking or even mode locking. When magnetic fluctuation becomes large enough during braking or locking, the resulting high amplitude saturated mode leads to subsequent or immediate collapse at the q = 2 rational surface.